2020
DOI: 10.1177/1557085120908332
|View full text |Cite
|
Sign up to set email alerts
|

Adolescence, Empathy, and the Gender Gap in Delinquency

Abstract: I propose the gender gap in delinquency is linked to adolescents’ orientation to gender-normative behavior and empathic development. I use longitudinal data on 1,525 youth from the Denver Youth Survey to analyze relationships among gender, empathy, and delinquency. I find girls exhibit higher levels of empathy across adolescence than do boys, and these differences emerge in preadolescence. Empathy is inversely related to delinquency, and is predictive of fraud and theft, but not violent delinquency. Finally, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 92 publications
1
14
0
1
Order By: Relevance
“…and could affect aspects of criminal behavior, including severity or persistence in the behavior (O'Neill, 2020). The results support our third hypothesis, proposing that EI and empathy predict decision-making styles in adolescent offenders and non-offenders, although we observed that the processes occur differently; these differences in effects were also seen in how the variables are related in adolescent offenders and non-offenders.…”
Section: Article In Presssupporting
confidence: 84%
See 2 more Smart Citations
“…and could affect aspects of criminal behavior, including severity or persistence in the behavior (O'Neill, 2020). The results support our third hypothesis, proposing that EI and empathy predict decision-making styles in adolescent offenders and non-offenders, although we observed that the processes occur differently; these differences in effects were also seen in how the variables are related in adolescent offenders and non-offenders.…”
Section: Article In Presssupporting
confidence: 84%
“…Evidence indicates that teen offenders show less empathy than their peers in the community (Lardén et al, 2006;Robinson et al, 2007). Empathy has also been observed to be inversely related to crime, and low empathy may be a predictor of criminal behavior (O'Neill, 2020).…”
Section: Emotional Intelligence and Empathy In Offendersmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond antisociality, a variety of criminal behaviours have also been associated with weak empathy; such as violent (Trivedi-Bateman, 2015, 2019Romero-Martinez et al, 2016;Winter et al, 2017), sexual (Hempel et al, 2015), and fraudulent (O'Neill, 2020) offending. Weak empathy is present in offending community samples (Jolliffe & Farrington, 2021d) and within juvenile incarcerated (Llorca-Mestre et al, 2017) and adult incarcerated offending populations (House et al, 2017;Jolliffe & Farrington, 2021d).…”
Section: The Relationship Between Weak Empathy and Antisocial And Criminal Behaviourmentioning
confidence: 99%
“…Scholars agree that empathy is critical for fathoming people's propensity for crime (Trivedi-Bateman, 2019). A lack of empathy has been found to increase the likelihood of a broad range of antisocial and criminal behaviours, among them violent (Shechtman, 2002;Romero-Martinez et al, 2016), sexual (Hempel et al, 2015;Loinaz et al, 2021) and fraudulent (Craig, 2017;O'Neill, 2020) offending as well as substance abuse (Martinotti et al, 2009;Ferrari et al, 2014) and bullying (Mitsopoulou & Giovazolias, 2015;Van Noorden et al, 2015). Thereby, the magnitude of the empathy effect seems to be contingent on the employed sampling frame and the investigated crime type.…”
Section: Empathymentioning
confidence: 99%